Exploring the Implementation of Islamic Work Ethics Among Muslim Women Workers - Rokhman, Wahibur (LPPM IAIN Kudus, 2022)
This study aims to understand the implementation of Islamic work ethics among working women in small and medium enterprises. This study used a questionnaire distributed to employees of SMEs, especially Muslim women in Kudus. Among the total of 300 questionnaires distributed, only 217 were returned, which related to the understanding of the role of women employees in the practice of Islamic work ethics. Based on the findings of the study, workers thrive in the five dimensions of Islamic work ethic, namely benevolence (ihsan), hardworking and maximum effort (mujahadah), competitiveness, self-discipline, and good intentions (niyyah). Muslim women workers have the knowledge and awareness to apply the Islamic work ethic by promoting Islamic values in the workplace. These results have implications for micro-entrepreneurs to implement a work ethic based on Islamic values because it positively affects the behavior of Muslim women workers.